A humanist appraisal of Foluke Ogunleyes jabulile (2018)
Humanism is “a system of thought centered on humans and their values, capacities, and worth. ” Humanism is an appeal to reason in contrast to revelation or religious authority as a means of finding out about the natural world and destiny of man, and also giving a grounding for morality...Humanist ethics is also distinguished by placing the end of moral action in the welfare of humanity rather than in fulfilling the will of God. ” Though the artist’s primary role is to entertain, based on the principle of socio-aesthetic harmony, it is obligatory for him or her to provide functional amusement. Humanism positions man at the centre stage of human existence and places on him the responsibility of making life meaningful, worth living and developmental. This has been the elemental pivot of humanistic drama from inception. This paper attempts an analytical review of Foluke Ogunleye’s Jabulile within the context of humanism. It argues that even though Ogunleye may not have been an avowed humanist (in the sense of its godlessness), her drama, with particular emphasis on Jabulile, subscribes to the tenets of cultural and literary humanism. The paper concludes that Ogunleye’s art does not only exemplify her humanistic disposition, it equally offers a panacea for the amelioration of the prevalent social dysfunctionalities in Nigeria